Innovative applications from marine macrobes - are sustainable exploitations of marine resources possible? - Silva, Tiago H. (2014)
Apresentação efetuada no New Frontiers in Blue Biotechnology : Research & SME Alliances in Early Drug Discovery : A Lunch Briefing (at the Invitation of Ulrike Rodust, MEP), Brussels, Beligum, 2014